Effective separation of surfactant-stabilized crude oil-in-water emulsions by using waste brick powder-coated membranes under corrosive conditions. Issue 4 (5th February 2020) - Shi, Guogui; Shen, Yongqian; Mu, Peng; Wang, Qingtao; Yang, Yaoxia; Ma, Siyi; Li, Jian
Abstract : Underwater superoleophobic WBP-coated membranes were employed to effectively separate crude oil-in-water emulsions under corrosive conditions. Abstract : Crude oil spill accidents that have been occurring frequently not only have been seriously destroying the marine ecological environment and threatening human health for a long time, but also generating a great loss of precious resources. Therefore, the treatment of crude oil wastewater, especially under corrosive conditions, is one of the most urgent problems. However, to the best of our knowledge, the effective separation of surfactant-stabilized micro-nanoscale crude oil-in-water emulsions under corrosive conditions has been rarely reported. Herein, waste bricks are employed to effectively separate the surfactant-stabilized micro-nanoscale crude oil-in-water emulsions under corrosive conditions, which not only enables the removal of crude oil, but also reduces environmental pollution. The suspensions of waste brick powders (WBP) and sodium alginate were coated onto a polyvinylidene fluoride (PVDF) membrane via a vacuum filtration approach to prepare a WBP-coated membrane. The as-prepared WBP-coated membrane exhibited excellent underwater superoleophobicity under corrosive conditions and low adhesion to crude oil. Besides, the WBP-coated membrane can separate crude oil-in-water emulsions with a separation efficiency of up to 99.8% and a permeating flux as high as 623 L m −2 h −1 . More significantly, the as-prepared WBP-coated membrane can successfully separate crude oil-in-water emulsions under corrosive aqueous conditions (1 M HCl, 1 M NaOH and 3.5 wt% NaCl solution) with a separation efficiency of above 99.5% and a permeating flux of up to 934 L m −2 h −1 . The WBP-coated membrane not only removes crude oil from oily wastewater, but also enables the recycling of waste resources.